2014
DOI: 10.1093/nar/gku1132
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster LRPPRC2 is involved in coordination of mitochondrial translation

Abstract: Members of the pentatricopeptide repeat domain (PPR) protein family bind RNA and are important for post-transcriptional control of organelle gene expression in unicellular eukaryotes, metazoans and plants. They also have a role in human pathology, as mutations in the leucine-rich PPR-containing (LRPPRC) gene cause severe neurodegeneration. We have previously shown that the mammalian LRPPRC protein and its Drosophila melanogaster homolog DmLRPPRC1 (also known as bicoid stability factor) are necessary for mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 55 publications
1
43
0
1
Order By: Relevance
“…Nevertheless, this modulation or another yet unidentified effect of the decreased expression caused the dysfunction of the mitochondria and damaged cell morphology. Similar effects of limited modulation of mitochondrial transcripts with significant mitochondria mis-functioning have been reported for the down regulation of the mitochondrial RNA-binding proteins LRPPRC and GRSF1 ( 15 , 25 ).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Nevertheless, this modulation or another yet unidentified effect of the decreased expression caused the dysfunction of the mitochondria and damaged cell morphology. Similar effects of limited modulation of mitochondrial transcripts with significant mitochondria mis-functioning have been reported for the down regulation of the mitochondrial RNA-binding proteins LRPPRC and GRSF1 ( 15 , 25 ).…”
Section: Resultssupporting
confidence: 71%
“…Because the protein is an endoribonuclease and exists as a monomer in the mitochondria, we proposed that LACTB2 plays an important role in mitochondrial gene expression. However, as with in other mitochondrial proteins involved in RNA metabolism, decreased expression of the protein and an analysis of the accumulation of mitochondrial transcripts failed to reveal its initial target ( 15 , 23 , 25 ).…”
Section: Resultsmentioning
confidence: 98%
“…PTCD3 is one of the mammalian mitochondrial pentatricopeptide repeat (PPR) domain proteins ( 23 ) that play a critical role in mitochondrial translation and organelle biogenesis and maintenance ( 17 , 24 ). During carcinogenesis, the material and energy in the cells are reshaped to support and help the survival of cancer cells and to satisfy the requirements for the synthesis of biological macromolecules and energy supplement in cancer cells ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the LRPPRC-SLIRP complex regulates mt-mRNA stability, polyadenylation and coordinated mitochondrial translation [ 17 ]. We have also demonstrated that the bicoid stability factor (BSF, renamed DmLRPPRC1), one of the two Drosophila melanogaster orthologues of mammalian LRPPRC [ 19 , 20 ], has a very similar function as the mammalian one [ 21 ]. Furthermore, DmLRPPRC1 associates with one of the two fly orthologues of SLIRP [ 19 , 21 ], suggesting that the interaction between PPR-motif- and RRM-containing proteins is important for mitochondrial RNA metabolism and has been conserved through evolution.…”
Section: Introductionmentioning
confidence: 99%